The Known Distribution and Ecological Preferences of the Tick Subgenus Boophilus (Acari: Ixodidae) in Africa and Latin America - Estrada-Peña, Agustín; Bouattour, A.; Camicas, J. -L.; Guglielmone, Alberto; Horak, I.; Jongejan, F.; Latif, A.; Pegram, R.; Walker, A.R. (Springer, 2020)
A compilation of the known distribution of Boophilus ticks in Africa and Latin America is presented, together with details on climate preferences. B. annulatus is recorded mainly in the western part of a strip from the equator to parallel 20° N. It associates with woodlands and forests (lowland rain forest and secondary grassland). This species is also present in the Mediterranean region, associated to woodland and open areas. B. decoloratus extends southern to parallel 20° N, in woodland with montane vegetation and Zambezian miombo; some records have been collected in the highveld grassland. B. geigyi is mainly collected in the western range of a stripe extending between parallels 5° N and 18° N, associated with Sudanian woodland, lowland rain forest with secondary grassland and woodland. Confirmed records of microplus in Africa are restricted to Malagasy region and south and eastern Africa, being predominant in the Zambezian miombo, deciduous forest with secondary grassland, and woodland. In Latin America, microplus is abundant in the Mesoamerican corridor to Venezuela and Colombia, and southern in Brazil and Argentina. The tick is mainly associated to the biomes of Chaco and Pampas in Argentina, the North-central moist Andes, the Atlantic forest (southern range) and the moist Meso-American vegetation (northern range). Most collections of B. annulatus and B. geigyi came from areas where winter minimum temperature is above 15 °C, maximum temperatures remain between 33 and 36 °C and maximum rainfall is recorded between June and September. B. decoloratus and African B. microplus are recorded in sites with low temperatures in May–September. Minimum temperature requirements are similar for both B. decoloratus and African B. microplus, and both are around 4 °C less than the value recorded for collections of Latin-American B. microplus. The rainfall pattern observed for decoloratus shows a minimum in May and June. The requirements of total rainfall are highest for B. microplus in Latin America, while records of African B. microplus are concentrated in areas of low rainfall between May and October, and high rainfall between November and March (low rainfall in the same period for B. decoloratus). Statistical analysis revealed the existence of populations (demes) with ecologically different requirements within each tick species. Both B. annulatus and B. decoloratus showed many different demes clearly associated to defined areas. The collections of Latin American B. microplus are very homogeneous according climate preferences and well separated from the African counterpart.